A kinetic model of phosphorus metabolism in growing goats - Vitti, D. M. S. S.; Kebreab, E.; Lopes, J. B.; Abdalla, A. L.; De Carvalho, F. F. R.; Resende, Kleber Tomás de [UNESP]; Crompton, L. A.; France, J. (My University, 2000)
The effect of increasing phosphorus (P) intake on P utilization was investigated in balance experiments using 12 Saanen goats, 4 to 5 mo of age and weighing 20 to 30 kg. The goats were given similar diets with various concentrations of P, and 32P was injected to trace the movement of P in the body. A P metabolism model with four pools was developed to compute P exchanges in the system. The results showed that P absorption, bone resorption, and excretion of urinary P and endogenous and fecal P all play a part in the homeostatic control of P. Endogenous fecal output was positively correlated to P intake (P < .01). Bone resorption of P was not influenced by intake of P, and P recycling from tissues to the blood pool was lesser for low P intake. Endogenous P loss occurred even in animals fed an inadequate P diet, resulting in a negative P balance. The extrapolated minimum endogenous loss in feces was .067 g of P/d. The minimum P intake for maintenance in Saanen goats was calculated to be .61 g of P/ d or .055 g of P/(kg.75·d) at 25 kg BW. Model outputs indicate greater P flow from the blood pool to the gut and vice versa as P intake increased. Intake of P did not significantly affect P flow from bone and soft tissue to blood. The kinetic model and regressions could be used to estimate P requirement and the fate of P in goats and could also be extrapolated to both sheep and cattle.
Keywords: Goats; Metabolism; Mineral Absorption; Phosphorus; Simulation Models; phosphorus; animal; animal food; biological model; cattle; chemistry; eating; feces; female; goat; growth, development and aging; kinetics; male; metabolism; Animal Nutrition Physiology; Animals; Cattle; Eating; Feces; Female; Kinetics; Male; Models, Biological